Impact of South Asian monsoon on summer dust weather occurrence over the Tarim basin in Northwest China. (14th October 2020) - Meng, Lixia; Zhao, Yong; Huang, Anning; Wang, Tianzhu; Wu, Yang
Abstract: Based on the observed dust weather occurrence (DWO), precipitation and 10 m wind speed at 23 stations over the Tarim Basin in northwest China and the National Centers for Environment Prediction/National Center for Atmospheric Research reanalysis data during 1961–2015, we have indicated the relationship between the summer DWO over the Tarim basin and South Asian summer monsoon (SASM) and revealed the possible underlying physical mechanisms. Results show that the DWO displays an obvious declining trend during 1961–2015 and has a good relation with precipitation and 10 m wind speed over the Tarim Basin in summer. Meanwhile, the index of SASM well correlates with the summer DWO over the Tarim basin at both interannual and interdecadal time scales. Further analysis of the underlying mechanism related to the impact of the SASM on the DWO over the Tarim Basin in summer indicates that an anomalous cyclone (anti-cyclone) appears in the upper troposphere over Central Asia responding to an anomalous anti-cyclone (cyclone) in the lower troposphere over Indian monsoon region during weak (strong) SASM years, which can cause cooling (warming) at middle and upper troposphere over Central Asia. Based on the relationship of thermal wind, the cooling (warming) results in an anomalous cyclone (anti-cyclone) at middle and upper troposphere over Central Asia and the anomalous south (north) winds prevail over the Tarim Basin. The south (north) winds are favorable for more (less) precipitation formation and inhibit (promote) the cold (warm) air entering into the basin and weaken (strengthen) the 10 m wind speed, further leading to the decreases (increases) of DWO over the Tarim Basin in summer.